DETERMINANTS OF THE QUALITY OF BUMDES FINANCIAL STATEMENT IN ALALAK DISTRICT - Rifqi Novriyandana; Lailata, Nadhifa Tahta (Jurnal Trial Balance, 2024)
BUMDes is the government's bid to improve the welfare of rural communities, but many are still troubled by poor quality financial reports. The purpose of this study was to determine how the quality of BUMDes financial reports in Alalak sub-district is influenced by human resource competence, information technology utilization, and internal control systems. This research uses quantitative methods. The purposive sampling method was used to determine the research sample. The selected sample consists of advisors, supervisors, directors, secretaries, treasurers, and financial staff from 10 BUMDes that are still operating in Alalak sub-district. The analysis in this study is in the form of data quality tests, classical assumption tests, hypothesis tests, and multiple linear regression tests using the SPSS version 25 program. The findings indicated that the competence of human resources and the use of information technology positively influenced the quality of BUMDes financial reports in the Alalak sub-district. However, the variable of the internal control system was found to have no impact on the quality of these financial reports in the same area.